Relic Particle Production - Valenzuela, Mississippi (2022)
The last few decades have seen an explosive increase in the amount and precision of data obtained from cosmological observations. Theoretical cosmologists have not yet finished interpreting this amount of data. Likewise, the wonderful ideas we have for the beginning of the Universe have not yet been connected with concrete models of elementary particles. Currently, the existence of dark matter (DM) is accepted in the scientific community. Stars, planets, comets, cosmic dust and other forms of matter make up 5% of the matter in the Universe. The remaining 95% would be "dark matter" and "dark energy", if it is that, it is not known what it is, in fact they exist. In this work, the standard cosmological model is studied, as well as the production of relic particles with the Boltzmann equation applied to the decoupling of relic particles from a reservoir.